A study on Contact Algebra by Browerian Logic - Pathak, Surendra Raj; Yadav, Raj Narayan (Amrit Research Journal, 2020)
There is a close relation between Boolean logic or two-valued logic and an electric di-contact algebra. Two-valued logic is concerned with propositions which are either true or false and which can be combined in various ways. Similarly, the switches of circuits are activated by contacts which, open or closed, can be combined in analogous ways. But there are positions which are not two-valued - a generalisation of truth values of a proposition leads to an n-valued logic. It is then natural to raise the query whether it is possible to generalise the notion of switching contact analogous to the generalisation of truth value of a proposition. If it is so, does there exist an isomorphism between propositional algebra in n-valued logic and a structure in switching circuits based on contact values? The solution of the problems leads to a new algebra. Here we have reviewed this contact algebra by Browerian logic.